FACTORS AFFECTING INDONESIAN PUBLIC HEALTH CENTERS' HEALTH WORKERS' INCOME ADEQUACY - Armedy Ronny Hasugian; Jaslis Ilyas; Harimat Hendrawan; Adang Bachtiar (Universitas Airlangga, 2023)
Background: Dissatisfaction, additional work, and desired compensation are related to the needs and perceptions of civil servant health workers to increase their income. However, the probability and influencing factors regarding the income adequacy of civil servant health workers in Indonesia are still unknown. Aims: to find out the factors related to the income adequacy of health workers. Methods: This observational study with a cross-sectional design uses data from the Employment Research in the Health Sector (RISNAKES) 2017 in Public Health Centers in Indonesia. Probit analysis was conducted to assess the probability of income adequacy. Results: A total of 963 respondents were analyzed. The study found that changes in each variable, including income, official residence facilities, training facilities/ seminars/ training, motivation, and job satisfaction of a unit, would increase the probability of income adequacy ranging from 2% - 81%, except for the age variable. By referring to high job satisfaction of > 75% and taking into account the probability of 80%, the presumed adequate income is no less than IDR 28,800,000. Conclusion: The probability of the monthly income adequacy of civil servants in the health sector is influenced by job satisfaction, ability to save, official residence facilities, facilities to attend seminars, age, and income. Increasing and reformulating the amount of income must be done to optimize the performance and productivity of health workers. Keywords: health workers, income adequacy, public health center, saving